Health Belief Model-Based Education for Stroke Patient Families: A Research and Development Study - Handayani, Luh Titi (International Journal of Multi Discipline Science (IJ-MDS), 2025)
This study aims to develop educational media based on the Health Belief Model (HBM), to analyse the effectiveness of this educational media in terms of the HBM, and to enhance family capacity. Using a modified Borg & Gall model, this study employed a Research and Development (R&D) methodology. The process included a needs analysis, product design, expert validation, limited testing, and subsequent adjustments. The efficacy of an educational pamphlet based on HBM in enhancing the knowledge and caregiving abilities of carers was evaluated. Purposive sampling was used to choose thirty stroke carers from Jember, Indonesia, with a minimum caregiving duration of at least one month. Pre- and post-tests, as well as HBM-based perception questionnaires, were used to gather data. Descriptive statistics, the Wilcoxon signed-rank test, and thematic analysis were used for analysis. The leaflet's quality was confirmed by the high Content Validity Index (CVI = 0.88) obtained through validation by three experts. Following the intervention, the percentage of carers with low knowledge decreased from 40% to 7%, while the percentage of carers with good knowledge grew considerably from 13% to 67% (p < 0.05). Furthermore, 76.7% of participants provided positive feedback, emphasising the leaflet's utility, clarity, and simplicity. Improvements in carers' motivation, self-assurance, and comprehension of stroke care were revealed by thematic analysis. Stroke carers' knowledge and self-efficacy were both improved by the HBM-based educational pamphlet. Knowledge retention and behavioural modification were facilitated by the well-organised, understandable content and visually appealing design. These results highlight the value of empowering families to provide long-term stroke care at home by utilising theory-based, easily navigable instructional resources.